A pipeline for high precision partial differential equation computation - Pan, W (2021)
In this thesis, we investigate the application of the cubature on Wiener space method(also known as the Kusuoka-Lyons-Victoir algorithm) to solving parabolic type lin-ear partial differential equation problems. The framework for the cubature methodwas first developed in the seminal paper [Lyons and Victoir, 2004]. Since then,several key ideas have been introduced to improve the method’s computationaltractability, hence practicality, without affecting its approximation order. We re-view these ideas in chapter 1.